A Comparative Analysis Of The Use Of Unsolicited Proposal For The Delivery Of Public-Private Partnership Projects In Africa - Nwangwu, George (Journal of Sustainable Development Law and Policy, 2025)
As countries across Africa continue to look for ways to develop their infrastructure, the use of Unsolicited Proposals (USPs) in the procurement of Public-Private Partnership (PPP) projects have become very popular across the continent. This is despite the widely held view that this procurement model should be used with caution since it stifles competition, is susceptible to abuse and, therefore, likely to lead to the delivery of projects that do not deliver value for money. However, apart from a few studies and despite the very pervasive use of USPs across the continent, there has been very minimal academic inquiry on the use of this procurement approach in Africa. This article, therefore, contributes to this very important area by first distilling a best practice framework as a guide for countries to use in procuring USPs. Secondly, the paper evaluates the experiences of four different African countries in the use of USPs, using the framework as a guide. The lessons learnt are then used to make recommendations for improvement in the procurement of USPs across Africa.